2020
DOI: 10.1364/oe.386204
|View full text |Cite
|
Sign up to set email alerts
|

Optical needles with arbitrary homogeneous three-dimensional polarization

Abstract: we propose a new method to generate optical needles by focusing vector beams comprised of radially polarized component and azimuthally polarized vortex components. The radial part can generate longitudinal polarization, while the azimuthal parts can generate left-and right-handed polarization. Hence, an arbitrary 3D polarization can be obtained. To our knoeledge, it may be the first time that arbitrarily polarized optical needles whose transverse sizes are under 0.5λ have been achieved. And their polarized hom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Tight-focusing vector beams were an effective method to generate optical needles that own the above properties. By now, reversed dipole radiation arrays, paraxial spherical mirrors focusing, 4π focusing system, and wavefront modulation were the main methods for the generation of optical needles by tight focusing vector beams [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In addition, some special methods were used to generate ultra-long optical needle.…”
Section: Introductionmentioning
confidence: 99%
“…Tight-focusing vector beams were an effective method to generate optical needles that own the above properties. By now, reversed dipole radiation arrays, paraxial spherical mirrors focusing, 4π focusing system, and wavefront modulation were the main methods for the generation of optical needles by tight focusing vector beams [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In addition, some special methods were used to generate ultra-long optical needle.…”
Section: Introductionmentioning
confidence: 99%
“…The ptical needle, also called a light pin, with a homogeneous axial intensity distribution and small full width at halfmaximum (FWHM) of cross-section, has become a hot topic of scientific research in recent years, because of its important applications, such as optical manipulation [1,2], particle acceleration [3][4][5], optical trapping [6][7][8][9], high-density optical datastorage [10][11][12], fluorescent imaging [13][14][15] and so on. Many scholars have reported the production of uniformintensity optical needles [16][17][18][19][20][21][22][23]. In 2008, Wang et al [19] reported for the first time that a purely longitudinally polarized optical needle with sub-diffraction beam size (0.43λ) and long depth of focus (∼4λ) was generated by focusing a * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the field in the focal region of an optical system with high numerical aperture has received much attention in the last two decades, because of its potential applications in microlithography, image processing, diffractive optics, adaptive optics, or holographic data storage [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Furthermore, the analysis of the on-axis intensity of highly focused optical fields has also proven to be of much practical interest, because it allows us to design structures such that their behavior along the axis can be modulated [7,9,11,[14][15][16]20].…”
Section: Introductionmentioning
confidence: 99%